Hydrazones and Thiosemicarbazones Targeting Protein-Protein-Interactions of SARS-CoV-2 Papain-like Protease - Ewert, Wiebke; Günther, Sebastian; Miglioli, Francesca; Falke, Sven; Reinke, Patrick Y. A.; Niebling, Stephan; Günther, Christian; Han, Huijong; Srinivasan, Vasundara; Brognaro, Hévila; Lieske, Julia; Lorenzen, Kristina; et al. (Frontiers in Chemistry, 2022)
The papain-like protease (PLpro) of SARS-CoV-2 is essential for viral propagation and, additionally, dysregulation of the host innate immune system. Using a library of 40 potential metal-chelating compounds we performed an X-ray crystallographic screening against PLpro. As outcome we identified six compounds binding to the target protein. Here we describe the interaction of one hydrazone (H1) and five thiosemicarbazone (T1-T5) compounds with the two distinct natural substrate binding sites of PLpro for ubiquitin and ISG15. H1 binds to a polar groove at the S1 binding site by forming several hydrogen bonds with PLpro. T1-T5 bind into a deep pocket close to the polyubiquitin and ISG15 binding site S2. Their interactions are mainly mediated by multiple hydrogen bonds and further hydrophobic interactions. In particular compound H1 interferes with natural substrate binding by sterical hindrance and induces conformational changes in protein residues involved in substrate binding, while compounds T1-T5 could have a more indirect effect. Fluorescence based enzyme activity assay and complementary thermal stability analysis reveal only weak inhibition properties in the high micromolar range thereby indicating the need for compound optimization. Nevertheless, the unique binding properties involving strong hydrogen bonding and the various options for structural optimization make the compounds ideal lead structures. In combination with the inexpensive and undemanding synthesis, the reported hydrazone and thiosemicarbazones represent an attractive scaffold for further structure-based development of novel PLpro inhibitors by interrupting protein-protein interactions at the S1 and S2 site.